Identifying the Shocks behind Business Cycle Asynchrony in Euroland - Carsten Trenkler; Enzo Weber (University of Mannheim, Department of Economics, 2012)
This paper investigates which shocks drive asynchrony of business cycles in the euro area. Thereby, it unites two strands of literature, those on common features and on structural VAR analysis. In particular, we show that the presence of a common cycle implies collinearity of structural impulse responses. Several Wald tests are applied to the latter hypothesis. Results reveal that differences in the GDP dynamics in several peripheral countries compared to a euro zone core are triggered by idiosyncratic, and to a lesser extent also world, shocks. Additionally, real shocks prove relevant rather than nominal ones.
urn:nbn:de:bsz:180-madoc-317082
Keywords: C32; E32; 330; Common cycles; euro area; impulse responses; structural VAR; Wald tes